Utilization of fluorescence spectroscopy as a novel approach to evaluate the oxidative stability in beef retail displayed - Pouzo, Laura Beatriz (2016)
Beef samples from grazing steers finished with different seed-supplemented diets were vacuum packaged for 3, 14 and 56 days (VC) and subsequently exposed to aerobic conditions (AE) for 0 and 5 days. Different fluorescent compounds of interest in the oxidation process were detected in meat, namely tryptophan residues, Schiff bases and porphyrins. Tryptophan intensity fluorescence increased with 14 days of VC; while Schiff bases intensity increased (P < 0.05) in beef samples stored under VC-56 and in all samples after AE-5 days. Porphyrins increased (P < 0.05) gradually with the extension of vacuum storage time, but were degraded in beef with long vacuum storage and 5 days of AE. Higher levels of porphyrins in beef under VC were correlated (P < 0.05) with lower redness and higher TBARS after AE-5. This study revealed the potential of fluorescence signals to detect oxidative changes in beef under different storage conditions using a fast and nondestructive method such as fluorescence spectroscopy.